Efektivitas Suku Badan Kesatuan Bangsa dan Politik dalam Rangka Menjaga Kerukunan Umat Beragama di Kota Jakarta Timur - Rifqi Farhan Fadhillah; Mawar Mawar (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
The main role of Suku Badan Kesbangpol is to facilitate the coordination and integration of national and political activities so that the goal of building community harmony can be realized more effectively and efficiently through empowering the role of Suku Badan Kesbangpol. The effectiveness of the organization in this study uses 3 (three) indicators, namely based on goal achievement, integration and adaptation. The purpose of this study is to determine and analyze the effectiveness of Suku Badan Kesatuan Bangsa and Politik in maintaining religious harmony in East Jakarta and also to determine and analyze what factors are supporting and inhibiting it. The research method used is a descriptive method with a qualitative approach. Determination of informants in this study used a purposive sampling technique. The effectiveness of Suku Badan Kesatuan Bangsa and Politik can still be said to be ineffective. This is because the three indicators used to measure this effectiveness have not been fully achieved. The three indicators are goal achievement, integration and adaptation. The achievement of goals carried out by Suku Badan Kesatuan Bangsa and Politik can be said to be effective because it goes through a series of processes in achieving goals. The integration indicator is still less effective, this can be seen from the occurrence of several conflicts that are still occurring in East Jakarta. The National Unity and Politics Agency is still not effective in countering the SARA issues that occur, meaning that the socialization carried out still needs to be improved. In the adaptation indicator, it is known that the East Jakarta National Unity and Politics Agency has been able to align various changes that occur in society, meaning that this adaptation indicator can be said to be effective.